Training Needs for Mothers of children With Autism Spectrum Disorder and it’s Relation with Some Variables - Alrefaay , Alia; Abo Hasan, Fadia (Latakia University Journal - Arts and Humanities Sciences Series, 2019)
This study aims to investigate the needs of Mothers of Children with Autism Spectrum Disorder in Damascus, according to educational level of mothers, severity of autism and gender of child. The researcher adopted the descriptive approach to achieve the aim of the study. The sample consisted of (78) mothers selected randomly. The researcher developed a questionnaire to explore the needs of those mothers, the questionnaire was in two parts consisting of (46) items the first part about theoretical knowledge it consisted of (20) items, the second was about practical skills it contained (26) items. The degree of validity and reliability of the questionnaire was good, so Cronbach's Alpha equation that which reach (0.97). . The findings of the study indicated, the degree of estimation of mothers of children with autism disorder to their training needs is high on theoretical knowledge domain and practical skills domain and on the whole questionnaire. The results also showed there are statistically significant differences between degree of training needs of mothers attributed to their educational level and to the severity of the child's disorder , and there are no found significant differences between degree of training needs of mothers attributable to gender of child. Based on the findings of the study the researcher pointed out the need of conducting more studies on new samples of mothers, with other variables, and on samples, including parents and brothers, and recommended increasing attention to training families of children with autism spectrum disorder, especially mothers, through the preparation of periodic training programs by centers that are concerned with these children.